Legal Protection of Coastal Community Rights in the Development of the Indah Kapuk 2 Beach Area: An Agrarian Law Perspective - Haspada, Deny; Juli Asril; Ryan Faisal; Saputra, Ade Rizki; Herdiyanti, Siti Handayani; Gunati, Mira; Mardiansah, Songgi (PT FORMOSA CENDEKIA GLOBAL, 2025)
Coastal development projects, such as Pantai Indah Kapuk 2 (PIK 2), have createdsignificant legal and social challenges for long-established coastal communities.This study aims to analyze the legal protection of coastal communities' rights in thedevelopment of PIK 2 from the perspective of agrarian law. Using a normativejuridical method and qualitative analysis, the study reveals a gap between existingregulations and the implementation of coastal community rights protection. Landconflicts emerge as a major issue due to unclear land ownership status and weakcompensation mechanisms implemented by developers. Furthermore, the lack ofcommunity participation in planning processes exacerbates the socio-economicimpacts they experience. Compensation mechanisms tend to focus solely oneconomic value without considering the social and cultural aspects inherent incoastal communities. This study highlights the need for policy reforms in protectingcoastal community rights, including strengthening regulations, ensuringtransparency in compensation mechanisms, and increasing community involvementin decision-making processes. More equitable and sustainable policyimplementations are expected to create a balance between development interests andthe protection of coastal community rights